Rapid minimally invasive subsurface archaeological site prospection on Roti Island, Indonesia - Kasih Norman; Kelsey Lowe; Matthew Forbes; Thomas Sutikna; Anton Ferdianto; Rachel Wood; Stewart J. Fallon; Rebecca Esmay; Jatmiko; I Putu Yuda Haribuana; I Made Agus Julianto; Ashleigh J. Rogers; et al. (Quaternary International, 2026)

Differentiating vegetation and environmental conditions using soil phytolith assemblages: insights from a bioclimatic gradient across northern Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Tim J. Cohen (Plant and Soil, 2025)
Background and Aims Analysis of fossil phytolith assemblages from palaeoecological and archaeological sites relies on the development of robust modern reference material from soils. This study investigates the utility of soil phytolith assemblages for characterising vegetation and environmental conditions across northern Australia and develops new validated phytolith indices for palaeoenvironmental reconstruction. Methods Phytoliths were extracted from 29 surface soil samples from ten vegetation types across a latitudinal bioclimatic gradient of northern Australia. Soil phytolith assemblages were compared with vegetation survey data and bioclimatic and edaphic variables. Redundancy analysis, linear discriminant analysis, and correlation analyses were used to explore relationships and evaluate the discriminatory power of environmental variables and morphotypes. Finally, the effectiveness of commonly used and proposed regional phytolith indices is evaluated. Results Soil phytolith assemblages broadly represent overlying vegetation communities but more clearly capture regional bioclimatic patterns. Statistical analyses reveal that assemblage composition is primarily driven by the latitudinal precipitation gradient, with Panicoideae phytoliths showing a promising positive correlation with mean annual precipitation. Two proposed phytolith indices (Iws and NA Ip) outperform the commonly used D:P ratio and Iph index and show strong potential for reconstruction of bioclimatic conditions. Conclusions This study demonstrates the potential of phytoliths to characterise vegetation and climatic patterns in northern Australia. Soil phytolith assemblages reflect changes in grass community composition and tree cover associated with the latitudinal precipitation gradient, and the proposed indices provide a framework for detecting past environmental variability. These findings highlight the utility of phytoliths for palaeoenvironmental research across northern Australia.

Globalism, localism and blue food systems – How can cross-scale tensions be reduced? A production perspective from UK seafood stakeholders - Alex J. Caveen; Bryce D. Stewart; Cameron Moffat; Daniel Skerritt; Estelle Jones; Huw Thomas; Lara Funk; Magnus Johnson; Mike Cohen; Michael Roach; Neil A. Auchterlonie; Samuel Peacock; et al. (Marine Policy, 2025)

Pleistocene stratigraphy and sedimentation in the Magadi-Ewaso Nyiro Basins, South Kenya Rift - R. Bernhart Owen; Robin W. Renaut; Tim K. Lowenstein; Mona Stockhecke; Nathan Rabideaux; Kennie Leet; Andrew S. Cohen; Jennifer J. Scott; Veronica Muiruri (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Australian subtropical vegetation and wetland response to fire, climate and nutrient availability during the Holocene - Haidee Cadd; Michela Mariani; John Tibby; Jonathan Tyler; Cameron Barr; Melanie J. Leng; Patrick Moss; Richard Lewis; Tim Cohen; Sam Marx; Glenn B. McGregor; Jonathan C. Marshall; et al. (Journal of Quaternary Science, 2025)
The iconic sand dune systems of Minjerribah (North Stradbroke Island), in southeastern Queensland, Australia, host numerous lakes and swamps containing organic‐rich sediment deposits that record changes in climate, fire and surrounding vegetation. Palaeoenvironmental reconstructions from individual locations can provide insights into changes in the environment, but determining the regional extent of these changes is seldom possible from a single site. Multi‐site compilations help elucidate the geographical nature of environmental changes and determine if they are driven by local or regional forces. Here, a synthesis of palynological records from six Minjerribah wetlands using a muti‐tiered Monte Carlo empirical orthogonal function (EOF) analysis allows island‐wide patterns of vegetation change to be identified. Coherent changes in vegetation were recorded, with first‐order changes (EOF1) indicating a long‐term shift in vegetation composition from closed forests towards woodland and heath vegetation. A compilation of macroscopic and microscopic charcoal from the same sites shares coherent patterns of change with a rainfall record from the island, suggesting that regional fire occurrence between 7000 and 2000 cal a bp was driven primarily by long‐term variations in rainfall and its influence on biomass. Comparison with fire activity, rainfall, sedimentary carbon, nitrogen and dust records from Minjerribah suggests that regional vegetation changes occur primarily in response to long‐term changes in nutrients and increasing rainfall variability. This analysis highlights the multi‐millennial connection between vegetation composition, climate, nutrients and fire occurrence across the Holocene in subtropical environments.

Temperature and hydrological change in central Australia through the last glacial cycle: Insights from clumped isotope analysis of lacustrine molluscs - Fletcher C. Nixon; Jonathan J. Tyler; Robert M. Klaebe; Stacey C. Priestley; Quan Hua; Lee J. Arnold; Tim J. Cohen (Quaternary Science Reviews, 2025)

Taxonomic and environmental significance of Poaceae and Cyperaceae phytoliths from the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Woody plant phytolith morphology and representation in surface sediments across the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Busting the dust: Evaluating local vs distal sources in Quaternary sediments at Thirlmere Lakes - Matthew S. Forbes; Samuel K. Marx; Tim J. Cohen; Bryce Sherborne-Higgins; Alexander Francke; Germanas Peleckis; Brian G. Jones; Anthony Dosseto; Haidee Cadd; Elizabeth Swallow; Mark Raven; Dioni I. Cendón; et al. (Applied Geochemistry, 2024)

Sea level rise drowned a vast habitable area of north-western Australia driving long-term cultural change - Kasih Norman; Corey J.A. Bradshaw; Frédérik Saltré; Chris Clarkson; Tim J. Cohen; Peter Hiscock; Tristen Jones; Fabian Boesl (Quaternary Science Reviews, 2024)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

The Effect of Mindfulness-based Programs on Cognitive Function in Adults: A Systematic Review and Meta-analysis - Tim Whitfield; Thorsten Barnhofer; Rebecca Acabchuk; Avi Cohen; Michael Lee; Marco Schlosser; Eider M. Arenaza-Urquijo; Adriana Böttcher; Willoughby Britton; Nina Coll-Padros; Fabienne Collette; Gaël Chételat; et al. (Neuropsychology Review, 2022)
Mindfulness-based programs (MBPs) are increasingly utilized to improve mental health. Interest in the putative effects of MBPs on cognitive function is also growing. This is the first meta-analysis of objective cognitive outcomes across multiple domains from randomized MBP studies of adults. Seven databases were systematically searched to January 2020. Fifty-six unique studies ( n = 2,931) were included, of which 45 ( n = 2,238) were synthesized using robust variance estimation meta-analysis. Meta-regression and subgroup analyses evaluated moderators. Pooling data across cognitive domains, the summary effect size for all studies favored MBPs over comparators and was small in magnitude ( g = 0.15; [0.05, 0.24]). Across subgroup analyses of individual cognitive domains/subdomains, MBPs outperformed comparators for executive function ( g = 0.15; [0.02, 0.27]) and working memory outcomes ( g = 0.23; [0.11, 0.36]) only. Subgroup analyses identified significant effects for studies of non-clinical samples, as well as for adults aged over 60. Across all studies, MBPs outperformed inactive, but not active comparators. Limitations include the primarily unclear within-study risk of bias (only a minority of studies were considered low risk), and that statistical constraints rendered some p -values unreliable. Together, results partially corroborate the hypothesized link between mindfulness practices and cognitive performance. This review was registered with PROSPERO [CRD42018100904].

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Middle Pleistocene to recent diatoms and stratigraphy of the Magadi Basin, south Kenya Rift - Veronica M. Muiruri; Richard Bernhart Owen; Gijs de Cort; Robin W. Renaut; Nathan M. Rabideaux; Tim K. Lowenstein; Kennie Leet; Mark Sier; Andrew Cohen; Dan Deocampo; Christopher J. Campisano; Anne Billingsley; et al. (Journal of Paleolimnology, 2021)

Sustainability assessment of a community open space vision - Matthew Cohen; John E. Quinn; Demi Marshall; Tim Sharp (Sustainability Science, 2019)

Revisiting an arid LGM using fluvial archives: a luminescence chronology for palaeochannels of the Murrumbidgee River, south‐eastern Australia - Daniela Mueller; Zenobia Jacobs; Tim J. Cohen; David M. Price; Ivars V. Reinfelds; James Shulmeister (Journal of Quaternary Science, 2018)
The Riverine Plain in south‐eastern Australia contains numerous palaeochannels that are much larger than the present rivers and provide evidence about past hydrological conditions. Previous research suggested optima in fluvial activity both before and after the peak of the Last Glacial Maximum (LGM; 21 ± 3 ka), and, in some cases, throughout the LGM. In this study, we revisit palaeochannel remnants of the Gum Creek and Yanco palaeochannel systems along the Murrumbidgee River, which drains the high‐elevation catchments of the Australian Alps in south‐eastern Australia. We date fluvial and aeolian sediments using single‐grain optically stimulated luminescence (OSL) and apply thermoluminescence (TL) dating to a subset of samples. We compare the OSL ages to new and previously published TL ages and investigate reasons for age discrepancies between these methods, possible effects of partial bleaching and other factors that may affect luminescence ages. We propose a new OSL‐based chronology for the Gum Creek and Yanco palaeochannel systems and assign periods of enhanced fluvial activity for the Tombullen and Yanco phases to 41–29 and 29–18 ka, respectively. Importantly, we infer that conditions of increased sediment and water discharge persisted for the Murrumbidgee River at the time of the LGM.

Late Quaternary channel and floodplain formation in a partly confined subtropical river, eastern Australia - James Daley; Jacky Croke; Chris Thompson; Tim Cohen; Mark Macklin; Ashneel Sharma (Journal of Quaternary Science, 2017)
Along the eastern margin of Australia, hydrological variability reaches a peak in the subtropics of south‐east Queensland and many rivers have entrenched characteristics. To address the nature of entrenchment and the relationship with adjacent alluvium, this paper presents the results of detailed chrono‐stratigraphic analysis of alluvial units in the partly confined mid‐reaches of Lockyer Creek, Australia. Four sites were investigated using topographic, sedimentological and chronological data. Radiocarbon and single grain optically stimulated luminescence dating indicate a large proportion of the valley fill reflects a major phase of aggradation of fine‐grained alluvium from ca . 35 ka throughout the Last Glacial Cold Period. Synchronous incision of Pleistocene alluvial fills between 11.5 and 9.3 ka suggests the current entrenched Lockyer Creek formed in response to changes in late Quaternary climate. Holocene floodplains set within the entrenched Pleistocene valley floor have basal ages of ca . 7.5 ka, but whose proximal margins are still actively accreting. This Holocene fill has accreted over the mid‐ to late Holocene but overlaps with the contemporary hydrological regime. The sedimentary nature of the Holocene fill appears to be related to persistent antecedent controls in the form of bedrock and terrace constriction.

What is the impact of systematically missing exposure data on air pollution health effect estimates? - Evangelia Samoli; Roger D. Peng; Tim Ramsay; Giota Touloumi; Francesca Dominici; Richard W. Atkinson; Antonella Zanobetti; Alain Le Tertre; H. Ross Anderson; Joel Schwartz; Aaron Cohen; Daniel Krewski; et al. (Air Quality, Atmosphere & Health, 2014)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Acute effects of ambient ozone on mortality in Europe and North America: results from the APHENA study - Roger D. Peng; Evangelia Samoli; Luu Pham; Francesca Dominici; Giota Touloumi; Tim Ramsay; Richard T. Burnett; Daniel Krewski; Alain Le Tertre; Aaron Cohen; Richard W. Atkinson; H. Ross Anderson; et al. (Air Quality, Atmosphere & Health, 2013)

A Multi-Tiered Analytical Approach For the Analysis and Quantitation of High-Molecular-Weight Aggregates in a Recombinant Therapeutic Glycoprotein - Heather Hughes; Charles Morgan; Elizabeth Brunyak; Kristen Barranco; Emily Cohen; Tim Edmunds; Karen Lee (The AAPS Journal, 2009)

On the derivation and tuning of phase oscillator models for lamprey central pattern generators - Péter L. Várkonyi; Tim Kiemel; Kathleen Hoffman; Avis H. Cohen; Philip Holmes (Journal of Computational Neuroscience, 2008)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Estimating the Strength and Direction of Functional Coupling in the Lamprey Spinal Cord - Tim Kiemel; Kevin M. Gormley; Li Guan; Thelma L. Williams; Avis H. Cohen (Journal of Computational Neuroscience, 2003)

Refined mapping of the gene for thiamine-responsive megaloblastic anemia syndrome and evidence for genetic homogeneity - T. Raz; Tim Barrett; Raymonde Szargel; Hanna Mandel; Ellis J. Neufeld; Kazuto Nosaka; Marcos B. Viana; N. Cohen (Human Genetics, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Estimation of Coupling Strength in Regenerated Lamprey Spinal Cords Based on a Stochastic Phase Model - Tim Kiemel; Avis H. Cohen (Journal of Computational Neuroscience, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)